Respuesta :

Answer: y-7 = 4(x+3), choice B

============================================

Point slope form is generally

y-y1 = m(x-x1)

we have m as the slope and (x1,y1) as the point this line goes through. In this case,

m = 4

(x1,y1) = (-3,7) so x1 = -3 and y1 = 7

So,

y-y1 = m(x-x1)

y - 7 = 4(x - (-3))

y - 7 = 4(x + 3)

which is why choice B is the answer

Point-slope form:

y - y₁ = m(x - x₁)    "m" is the slope


Since you know:

m = 4

(x₁ , y₁) = (-3,7)

You can plug it into the equation


y - y₁ = m(x - x₁)  

y - 7 = 4(x - (-3))

y - 7 = 4(x + 3)

Your answer is the 2nd choice